Effects of salinity on growth and lipid accumulation of biofuel microalga Nannochloropsis salina and invading organisms - Bartley, Meridith L.; Boeing, Wiebke J.; Corcoran, Alina A.; Holguin, F. Omar; Schaub, Tanner (Biomass & bioenergy, 2013)
Mass production of microalgae is currently limited by existing cultivation strategies, which rely heavily on open cultivation systems. Increasing lipid production in these systems while minimizing the invasion of non-target algae (competitors) and grazers (predators) will improve the economic viability of algal biofuel. In this study, we manipulate a basic environmental parameter, salinity, to promote algal growth and limit invading organisms. We monitor the growth of marine microalga Nannochloropsis salina and invasion of algal competitors and predators in open cultures grown at different salinities ranging from brackish to hypersaline. Algal growth and biomass was greatest at salinities of 22 and 34 PSU, whereas the density of invading organisms was lowest at 22 PSU. To determine if lipid accumulation could be maximized by salinity stress, we grew N. salina at 22 PSU until the populations were at stationary phase and then increased salinity to 34, 46, and 58 PSU. Gravimetrically determined lipid content increased significantly at these higher salinities, and was highest at 34 PSU (36% dry tissue mass). Analysis of Folch extracts by FT-ICR mass spectrometry showed a monotonic increase in triglyceride content and decreased membrane lipid content with increased salinity. Together, this work demonstrates an ecological approach to overcome the current limitations of cultivation strategies. •Marine microalgae Nannochloropsis salina can be grown for biofuel production.•We evaluate effects of salinity on algae growth, lipids and invading organisms.•N. salina growth fastest at salinities of 22–34 PSU.•Invading organisms are limited at 22 PSU.•Highest lipid accumulation is observed when salinity is changed from 22 to 34 PSU.